Establishment of a center of excellence in the field of remote sensing for cultural heritage at the Cyprus university of technology: the ‘ATHENA’ Horizon 2020 Twinning project - Hadjimitsis, Diofantos G.; Agapiou, Athos; Lysandrou, Vasiliki; Themistocleous, Kyriacos; Cuca, Branka; Nisantzi, Argyro; Lasaponara, Rosa; Masini, Nicola; Krauss, Thomas; Cerra, Daniele; Gessner, Ursula; Schreier, Gunter (My University, 2016)
This paper presents an overview of the “ATHENA” project which aims to establish a Center of Excellence in the field of Remote Sensing for Cultural Heritage in the areas of Archaeology and Cultural Heritage through the development of an enhanced knowledge base and innovative methods. This center will be established by twinning the existing Remote Sensing and Geo-environment Research Laboratory at the Cyprus University of Technology (CUT) with internationally-leading counterparts from other Member States of the EU, such as the Institute of Archaeological and Monumental Heritage (IBAM) and Institute of Methodologies for Environmental Analysis (IMAA) of the National Research Council of Italy (CNR) and the German Aerospace Centre (DLR). The goals of the Center will be aligned with the Smart Specialization Strategy of Cyprus and to the new European Cohesion Policy. The close collaboration between CUT and other experts in the field of Remote Sensing for Cultural Heritage in the EU will form a synergic network that will permit the transfer of knowledge and training of the existing personnel of CUT. As a result, the ATHENA project will have both direct and indirect social, scientific, and economic outcomes. In addition, the implementation of the project will facilitate future collaborations with experts of the Archaeology and Cultural Heritage sector in an EU level and in the region, increase the Centers’ research capabilities, as well as enhance the research and academic profile of all participants. It is noteworthy to underline the importance of the geographical position of the Center in the region of eastern Mediterranean, a region inhabited thousands of years before and therefore abound in archaeological residues.
Keywords: Cultural Heritage; Remote sensing; Cyprus; Center of excellence